2015
DOI: 10.1016/j.jadohealth.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Mother–Son Communication About Sex and Routine Human Immunodeficiency Virus Testing Among Younger Men of Color Who Have Sex With Men

Abstract: Purpose To document the HIV testing behaviors and serostatus of younger men of color who have sex with men (YMSM), and to explore sociodemographic, behavioral, and maternal correlates of HIV testing in the past six months. Methods 135 YMSM aged 16–19 completed a close-ended survey on HIV testing and risk behaviors, mother-son communication, and sociodemographic characteristics. Youth were offered point-of-care HIV testing, with results provided at survey end. Multivariate logistic regression analyzed the soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 39 publications
0
22
1
Order By: Relevance
“…It may be that having important kin relationships is associated with better care outcomes, although having a mother figure did not modify the findings when added to the model. Previous work has shown that family in the lives of YBMSM matters with respect to HIV testing and other HIV related risk behaviors [38, 39]. Relatedly, network interventions have been found to be effective including group-level interventions [40], which may hold promise for improving the HIV care continuum [41].…”
Section: Discussionmentioning
confidence: 99%
“…It may be that having important kin relationships is associated with better care outcomes, although having a mother figure did not modify the findings when added to the model. Previous work has shown that family in the lives of YBMSM matters with respect to HIV testing and other HIV related risk behaviors [38, 39]. Relatedly, network interventions have been found to be effective including group-level interventions [40], which may hold promise for improving the HIV care continuum [41].…”
Section: Discussionmentioning
confidence: 99%
“…Index participants reported if they had ever used marijuana (52) and engaged in condomless anal sex with a male partner of unknown HIV status in the past 6 months (53). …”
Section: Methodsmentioning
confidence: 99%
“…The same metric and time frame assessed the frequency of CAS with a male partner of different/unknown HIV‐status, recoded as 0 ( no ), 1 ( yes ). All three items have been used in prior research with sexual and gender minority youth of color (Bouris, Hill, Fisher, Erickson, & Schneider, ). HIV‐serostatus was based on the results of an oral rapid HIV antibody test, with 0 ( negative ), and 1 ( positive ).…”
Section: Methodsmentioning
confidence: 99%